Using homeopathic medications to treat lung cancer (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2025)
Both in vitro and in vivo, in both people and animals, and in both lower and higher potencies,homeopathic medications have shown biological effect in the treatment of cancer. Cancer patients mustmake a life-or-death choice on their course of therapy. It would seem reasonable and worthwhile, evenurgent, to increase research on and even the provision of homeopathic treatment for lung cancer and otherdiseases, since the majority of conventional treatments are still linked to serious side effects andoccasionally fatal outcomes, whereas homeopathy has been found to be free of such effects.